ON IMPROVEMENT OF METHODOLOGY FOR CALCULATING THE INDICATOR «AVERAGE WAGE» - Oksana V. Kuchmaeva; Ljubov’ I. Ageeva; Pavel A. Smelov (Статистика и экономика, 2016)
The article describes the approaches to the calculation of the indicator of average wages in Russia with the use of several sources of information. The proposed method is based on data collected by Rosstat and the Pension Fund of the Russian Federation. The proposed approach allows capturing data on the wages of almost all groups of employees. Results of experimental calculations on the developed technique are present in this article.